Teaching Reading in Canada: Curriculum and Assessment Policy Updates from the Provinces and Territories - Sinclair, Jeanne; Nickel, Jodi; Fraser, Andrea; Brethour, Melanie; Critch, Tracy; Hope, Linsey; McCallum, Deb; Norris, Megan; St. Croix, Norma; Vieira, Ana; Worden, Jessica (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The Ontario Human Rights Commission's 2022 Right to Read report called for significant shifts in how reading is taught, emphasizing systematic, explicit instruction in foundational skills alongside meaning-focused objectives. The Commission's call to action has reverberated across Canada, prompting provinces and territories to reconsider curriculum, assessment, and teacher preparation. This paper surveys the recent history and current status of reading reforms in Canada, asking: How have curriculum, pedagogy, and assessment changed? Who are the key drivers, and what challenges remain? We analyzed governmental reports, policy documents, and personal communication with educational leaders to craft profiles of each province and territory. Findings suggest that while reforms are underway in many jurisdictions, implementation varies depending on resources, professional learning infrastructure, and political culture. We argue that sustainable change requires enhancing teacher knowledge, affirming professional autonomy, and integrating culturally responsive and equity-oriented approaches with structured and systematic instruction. Ultimately, Canada’s unique policy context presents both challenges and opportunities for literacy education that ensures all children's right to learn to read.